Respect and criminal justice - Watson, Gabrielle 1989- (Clarendon studies in criminology., 2020)
Respect and Criminal Justice offers the first sustained examination of 'respect' in criminal justice in England and Wales, where the value is elusive but of persisting significance. Advancing a critique of the 'respect deficit' in policing and imprisonment, the book is concerned with the ways in which both institutions are merely constrained and not characterised by respect. It emerges that they appeal to the word 'respect' - relying on its -inclusive ethos in official discourse when it is expedient to do so - but rarely and only superficially address the prior question of what it is to respect and be respected. The result is that respect is more akin to a slogan than a foundational value of criminal justice practice. The book will be of interest to academics and students across the humanities and social sciences and especially in law, criminal justice, and philosophy, as well as criminal justice practitioners and policymakers.